Bulk Etch Rate Measurement of Cr-39 Detector at Constant Normality Using The Diameters and The Lengths of The Tracks of Α-Particles - Ahmed, Hussein A. (Science Journal of University of Zakho, 2014)
The aim of this paper is to determine the bulk etch rate of Nuclear Track Detector (type CR-39) using the track’s diameter-length (Le-D) measurement method by irradiating the detector with different energies of alpha particles from 241Am source. Constant normality (6.25) N of the chemical solution NaoH at a temperature of (70±1) oC is used in etching the detectors to measure the track’s lengths and it’s diameter at different etching times corresponding to the energy of the incident’s particles. The bulk etch rate VB values of CR-39 detector have been found by using Le-D method are (1.4228, 1.2563, 1.5098, 1.438) µm.hr-1 and they showed good agreement with the values measured by the removed layer method which were (0.944-1.831) µm.hr-1.
Keywords: Bulk etch rate; CR-39; Track length; Nuclear Track Detector (NTD)